The Influence of Jigsaw Method on Anxiety and Self-efficacyin Learning a Foreign Language - Harnany Utami, Lufiana; Sulianti, Ambar; I , Nyoman Sudana Degeng; Harry Sulistyo, Gunadi; Chusniyah, Tutut (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: Although the Jigsaw cooperative learning method has long been known in the world, there is still less evidence of that application on foreign languages learning in Indonesia. This study aims to understand the effect of Jigsaw learning method on anxiety and self-efficacy, as well as to analyse the correlation between self-efficacy and anxiety in learning a foreign language. Methodology: This is an experimental study with a Pre-Post-Test with Control group design. Subjects are high school students who have high anxiety in learning a foreign language. The total subjects were 182 students who were divided into two groups, 92 students learned English with the jigsaw technique while 90 students with conventional lecturing. The experiment was conducted in 8 sessions. Measuring anxiety used The Foreign Language Classroom Anxiety Scale by Horwitz, Horwitz & Cope, while self-efficacy was modified from Self-efficacy Scale by Bandura. Wilcoxon signed-rank test was used to compare the difference between anxiety and self-efficacy on the pre-test and post-test group. Mann Whitney analysis was used to see the difference between experimental and control group. Furthermore, to determine the correlation between anxiety and self-efficacy, Spearman analysis was carried out. Results: The results showed that anxiety in experimental groups was significantly decreased. Communication apprehension is the dimensions that have the highest decreasing among three dimensions. Besides, there was a significant increase in self-efficacy in the Jigsaw group. There was also a negative correlation between self-efficacy and anxiety in learning foreign language anxiety. Applications/Originality/Value: This is the first study that reveal the relationship of Jigsaw methods to be applied in Indonesian high schools that rely on reading comprehension competencies and writing opinions. We suggest that the jigsaw method can be used as an alternative technique in learning a foreign language in Indonesian senior high school.